Correction of the skin microbiome dysbiosis as an integral part of causative treatment of atopic dermatitis - Yuliya G. Levina; Anna A. Alekseeva; Kamilla E. Efendiyeva; Elena A. Vishneva; Leyla S. Namazova-Baranova (Педиатрическая фармакология, 2019)
The review details the role of the skin microbiome dysbiosis in the pathogenesis of atopic dermatitis. Changes in the normal microbiota of the skin with massive colonization with Staphylococcus aureus may play a key role in the disease. Studies have shown that commensal bacteria (for example, Staphylococcus epidermidis) can suppress  the inflammatory response  in the skin by activating production of IL10 by antigen-presenting  cells. New therapeutic approaches are described, including the use of topical emollients containing active substances that have an immunomodulatory effect and positively affect the skin microbiome of children with atopic dermatitis.